Rainfall intensity (I)–duration (D) induced debris flow occurrences in Peninsular Malaysia - Kasim, Norhidayu; Abu Taib, Kamaruddin; Ghazali, N.A.A.; Wan Azahar, Wan Nur Aifa; Ismail, Norfarah Nadia; Md. Husain, Nadiah; Ramli, Ahmad Bukhari; Saad, Siti Asmahani; Masjuki, Siti Aliyyah; Ibrahim, Saerahany Legori (Springer, Cham, 2020)
This paper evaluates the rainfall-induced debris flow in Peninsular Malaysia from the perspective of rainfall threshold. Eight selected debris flow occurrences in Peninsular Malaysia have been used for this study. Rainfall records are obtained from the nearest meteorological station of Drainage and Irrigation Department and the Malaysia Meteorology Department. In order to determine the reasonable correlation of rainfall with the occurrence of debris flow, the relationship between rainfall intensity (I) and duration (D) has been analysed. Furthermore, to analyze the empirical rainfall threshold, the values of the maximum hourly rainfall intensity and durations that correlate with debris flow have been plotted along with the intensity against duration in log-log graph. Comparison made between the compiled Peninsular Malaysia data and the worldwide threshold value shows that the triggering threshold is mostly higher for the Peninsular Malaysia events. The presence of thicker soil layers are likely the reason of higher thresholds limit, as more rainfalls are required to cause extensive localized failures to occur.